The Nexus between Sharia Principles and Banking: Why Islamic Values Matter in Islamic Banking? - Syafril, Syafwendi (Penerbit Goodwood, 2025)
Purpose: This study aims to examine how Islamic principles and values serve as essential pillars in Islamic banking, distinguishing it from conventional practices. By analyzing the rationale behind prohibitions in Islamic banking, this research provides insights into their impact on stakeholders, clients, the Islamic banking industry, and society at large. Research Methodology: This study uses qualitative library research to explore the integration of Shariah principle in Islamic banking. Primary Islamic texts and secondary scholarly sources are reviewed systematically, and inductive thematic analysis highlights the ethical rationale behind prohibitions on interest (riba) and unethical investments, underscoring Shariah adherence as a foundational framework in Islamic finance. Results/Findings: Findings indicate that the adherence to Sharia principles within Islamic banks drives efficiency, risk protection, socio-economic benefits, such as wealth distribution, fair income distribution, sustainable growth, and social welfare. This provides a rational foundation for eliminating prohibited elements, emphasizing the broader social mission of Islamic banking. Conclusion: This study underscores the critical role of Sharia principles in Islamic banking, particularly emphasizing the prohibitions against riba, excessive uncertainty, and highly speculative investment. Limitations: This study focuses on the rationale behind prohibitions in Islamic banking broadly and does not empirically test the impact of each prohibition. Contribution: The study contributes to the field by rationalizing the importance of Sharia values in banking practices, illustrating how these principles create an ethical banking system that fosters mutual benefit rather than exploitation. This insight adds a nuanced perspective on the socio-economic benefits of non-interest-based banking models, which prioritize fairness and community welfare.